Learning Achievements at Graduate Level: Bloom's Taxonomy Analyze - Hartono Hartono (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
Improving high-level thinking skills (high order thinking) has become a basic requirement in national higher education. The problem is, has higher education in Indonesia implemented learning that improves the highest level thinking skills? It is common for national tertiary education at the undergraduate level to carry out learning that is oriented towards increasing the level of higher order thinking. To answer this question, research has been carried out through document analysis in the form of semester syllabus (RPS) for undergraduate level. Normatively, the undergraduate level has the task of making students at least able to apply theories/concepts/methods/rules/laws when carrying out learning. The revised version of Bloom's Taxonomy has formulated the levels of thinking that students must experience during learning, including the lowest level is 'remembering' and the highest level is 'creating'. The results of the document analysis show that the undergraduate level learning in most lesson plans still uses the word 'explain'. The word 'explaining' is an operationalization of the word 'understanding' which has two levels. This second level shows that learning in higher education is still at a lower level (low order thinking).